(untitled) (Theatrum historiae, 2013)
Living conditions of the ancient Egyptians were not as ideal as it might seem, considerring their perfect creations of art and architecture which we admire today. It reveals among other things short period of their life expectancy and gradual uncovering traces of disease in skeletons or mummies. It is not surprising that since the beginning of Egyptian civilization developed in Egypt from prehistoric art of healing independent discipline of medicine. With the increase of population density grew the number of doctors, whose quantity reached a peak during the New Kingdom period. Thanks to the invention of writing on papyrus scrolls could their empirical knowledge be passed on from generation to generation through medical texts. Apart from treatment manuals these medical texts contain historically the first scientific system, which tried to explained functions of healthy and sick organism. Some of the doctors have reached soon domain specialization, while others gained hierarchical titles counting as well the highest of them. Their excellent reputation has spread beyond the borders of Egypt, where in the 1st Millennium BC learned their practices adepts of Greek medicine. In the Ptolemaic Period grew up in Alexandria one of the most important centers of Greek medicine.